(untitled) (International Journal of Engineering and Computer Science, 2014)
Twitance is a recommendation and analytic tool for Twitter which would help Twitter users to find people on their particular interest so as to better engage with the audience. It works as a search engine of people. A website on which user can search for his topic related Twitter users and then afterwards use them as mentions in his tweet to increase his audience. Later on the user will be provided with the reach of his tweet. A graphical representation of who all have re-tweeted his tweet, made his tweet favorite, replied to his tweet and who among those re-tweeters have greater influence. He also gets to know who are the people who have similar interests to him.